2020
DOI: 10.3390/vaccines8010021
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic DNA Vaccines Adjuvanted with pIL-33 Drive Liver-Localized T Cells and Provide Protection from Plasmodium Challenge in a Mouse Model

Abstract: tr (A.S.I.A.) † These authors contributed equally to this work and are presented in alphabetical order.Abstract: The need for a malaria vaccine is indisputable. A single vaccine for Plasmodium pre-erythrocytic stages targeting the major sporozoite antigen circumsporozoite protein (CSP) has had partial success. Additionally, CD8+ T cells targeting liver-stage (LS) antigens induced by live attenuated sporozoite vaccines were associated with protection in human challenge experiments. To further evaluate protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Importantly, the three LS exported proteins used in this study were selected based on a previous study, which showed their potential induction of CD8 T cells and their role in conferring sterile protection against infectious sporozoites when tested individually [5]. Despite the fact that the correlates of protection for each of the LS exported proteins in this viral vaccine were not tested, it will be the goal of future studies to identify the correlates of protection for the antigens presented by this vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, the three LS exported proteins used in this study were selected based on a previous study, which showed their potential induction of CD8 T cells and their role in conferring sterile protection against infectious sporozoites when tested individually [5]. Despite the fact that the correlates of protection for each of the LS exported proteins in this viral vaccine were not tested, it will be the goal of future studies to identify the correlates of protection for the antigens presented by this vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…VC2 is safe and immunogenic in mice, guinea pigs, and non-human primates [4]. To produce a malaria vaccine, we selected the highly conserved malaria parasite proteins EXP1 (exported protein 1), TMP21 (transmembrane protein 21) and UIS3 (upregulated in infectious sporozoites), as they were the best LS exported protein candidates that showed, individually, the best results in protecting immunized mice against an infectious sporozoite challenge, and eliciting CD8 T cells in a previous DNA immunization study from our lab [5]. However, the best protection against a challenge was achieved when the three proteins were combined in intramuscular DNA immunization [5]; therefore, here, they were selected in a combination of three recombinant viral vaccines, each expressing one of the selected LS exported antigens.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Co-delivery of IL-2, for example, was observed to improve the immunogenicity of DNA vaccines against SARS-CoV S and N proteins, influenza H1N1 hemagglutinin and neuraminidase, and HIV gp120 and Nef (92)(93)(94). Co-delivery of DNA vaccine against liver-stage malaria antigens with IL-33 was found to improve liver-localized CD8+ T-cell responses and confer improved protection to mice from Plasmodium challenge (95). Co-administration of IL-36γ, on the other hand, was found to improve immune responses induced by DNA-encoded Zika, HIV and influenza vaccines, and reduced dose requirement of DNA vaccines in mice to protect against ZIKV challenge (96).…”
Section: Dna-encoded Cytokine Adjuvantsmentioning
confidence: 99%